2020
DOI: 10.1002/jbmr.4052
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing of Calvarial and Long-Bone Endocortical Cells

Abstract: Single-cell RNA sequencing (scRNA-Seq) is emerging as a powerful technology to examine transcriptomes of individual cells. We determined whether scRNA-Seq could be used to detect the effect of environmental and pharmacologic perturbations on osteoblasts. We began with a commonly used in vitro system in which freshly isolated neonatal mouse calvarial cells are expanded and induced to produce a mineralized matrix. We used scRNA-Seq to compare the relative cell type abundances and the transcriptomes of freshly is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 51 publications
5
51
1
Order By: Relevance
“…2b ), highlighting the close proximity of the E15.5 coronal suture to the chondrocranium. Myeloid cells were more abundant at E17.5, consistent with reports of increased myeloid differentiation during late embryonic stages 24 (Supplementary Fig. 2b ).…”
Section: Resultssupporting
confidence: 89%
“…2b ), highlighting the close proximity of the E15.5 coronal suture to the chondrocranium. Myeloid cells were more abundant at E17.5, consistent with reports of increased myeloid differentiation during late embryonic stages 24 (Supplementary Fig. 2b ).…”
Section: Resultssupporting
confidence: 89%
“…Potentially, there is also some expression in macrophages—possibly also in bone resorbing osteoclasts as these two cell types share a common origin—although the levels may be too low to affect the function of the cells 51 . We find that an effect of the transgene in osteoblasts is very unlikely, as single-cell sequencing RNA data showed that endogenous Fabp4 is expressed at extremely low levels in osteoblasts 52 . Although the literature directly (adipocytes) and indirectly (bone cells) confirm specificity of the adipocyte apoptosis, it is a limitation that we have not confirmed specificity ourselves.…”
Section: Discussionmentioning
confidence: 81%
“…The approach we have used appears to have advantages over microarray studies in a single species, allowing greater refinement of data to identify key regulators of the sitespecific characteristics of the skeleton. This has been underscored by a very recent study using scRNA-Seq, suggesting that osteoblasts isolated from calvaria and cortical long bone in mice have similar transcriptomes (12), although the authors suggest that changes after isolation of the cells may have contributed to the lack of differences identified. To impact upon bone pathology, therapies to make long bones behave more like the flat bones of the skull in respect of their susceptibility to loss in response to aging, disuse, and hormonal or nutritional changes could provide powerful methods to maintain bone strength throughout life and provide a strong biological explanation for the promising development of sclerostin antibodies for the treatment of osteoporosis (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the biological basis for site specific regulation of bone mass and structure we have used RNA sequencing to compare the transcriptomes of samples of skull and tibial bones from three species: mouse, rat, and rhesus macaque. Others have tried to address this question in the past, using bone samples (that included bone marrow) from young rats (10,11) and mice (12), identifying several 100 genes that appeared regulated differently between sites. The cross-species design allowed us to focus our results on what we believe are broad biological mechanisms, and resulted in only a relatively small number of differences between sites that were shared across species and are therefore likely to reflect mechanisms in humans.…”
Section: Introductionmentioning
confidence: 99%